The Phenomenon of School Bullying among Indonesian Senior High School Students: A Cross-Sectional Study - Nur Anisah Farhanah; Nor Fatmah (YASIN, 2026)
Although school bullying has received considerable scholarly attention, understanding of the psychological processes underlying bullying perpetration among high school students remains limited. This study aims to explore the psychology of bullying perpetrators by examining why students engage in aggressive behavior toward their peers. A qualitative descriptive approach was employed, with data collected through triangulation involving in-depth interviews, participant and non-participant observation, and documentation studies, including school records and incident reports. Informants were selected purposively based on their involvement in bullying incidents and demographic variation. Data were analyzed inductively using thematic analysis through data reduction, data presentation, and conclusion drawing, while validity was ensured through source and technique triangulation, member checking, and audit trails. The findings indicate that bullying behavior develops through habituation in social interactions, in which actions initially perceived as humorous or as attempts to gain peer approval are repeatedly reinforced by laughter, encouragement, and imitation. Key motivating factors include the need for recognition and dominance, emotional instability, low impulse control, past experiences of abusive treatment or authoritarian parenting, and unstable friendship patterns. However, some perpetrators developed moral awareness after recognizing the psychological impact of their actions on victims, indicating the potential for empathetic and rehabilitative interventions. These findings suggest that bullying is not merely the result of individual intention but emerges from complex interactions between internal factors, such as emotion and affective regulation, and external factors, including peer, family, and school environments. This study contributes to bullying prevention literature by highlighting the psychological and social mechanisms underlying perpetrator behavior and provides practical implications for integrated interventions, including social-emotional skills education, proactive school policies, parenting programs, and restorative approaches to support the recovery of both perpetrators and victims.